Geotechnical Behaviour of Gypseous Soil Treated by Geopolymer Additives - Tanya Ekram Mahmood; Majid Hussein Hamed; Ali Kadhim Ibrahim (Diyala Journal of Engineering Sciences, 2023)
Gypseous soil is well-known for its numerous engineering problems. When this soil is exposed to water, the gypsum in the soil dissolves, causing the buildings built on it to collapse; so, treating gypseous soil is important for improving its engineering characteristics. The present paper focuses on studying the effect of adding geopolymer on mechanical characteristics of gypseous soil. This study presents the results obtained from a series of experimental tests, including direct shear, consolidation, and collapsibility tests. Tests were conducted on samples of gypseous soil taken from depth 1.5 meters below ground level with gypsum content of 41%. The geopolymer was used in three different molarities for the collapse test (10M, 12M, and 14M) and a 14 molarity only for the shear and consolidation tests, where equal proportions of fly ash were combined with an alkaline activator that was composed of sodium hydroxide and sodium silicate. The binder (fly ash + alkaline) to the soil was added to the treated samples during mixing at a rate of 20% by weight. The findings showed that treating the soil with geopolymer leads to a notable enhancement in the angle of internal friction of the soil particles from (37 to 42) degrees. as well as a reduction in the soil compressibility and a reduction in the susceptibility of the soil to collapse, with an improvement degree of 64% when using a geopolymer with a molarity of 14 M. This improvement was achieved by using a geopolymer with a higher concentration of NaOH. The best results were achieved when a geopolymer with a molarity of 14 was used, which is the ideal ratio.